The FBI and the KKK: a critical history - Newton, Michael (McFarland & Company, 2005)
"This book begins with their first confrontation in 1922, and examines the similarities, covert collaborations and common goals of the FBI and the KKK. The book traces 80 years of parallel development and the conservative attitudes that drew the FBI and the KKK together, especially in the area of civil rights"--Provided by publisher